Analysis of Public Sector Coordination Implementation in Patuha 2 Geothermal Power Plant According To Public Private Partnerships (PPP) Framework (International Journal of Scientific Research and Management (IJSRM), 2022)
The development of national electricity infrastructure has become one of the national strategic programs, one of which is the construction of the Patuha 2 geothermal power plant conducted by PT. Geodipa Energi (GDE). The Patuha 2 project is implemented using the Public Private Partnership (PPP) scheme. The implementation of public sector coordination in the Patuha 2 project is an important element to supporting project success. Initial research data shows that there are problems in the implementation of public sector coordination in the Patuha 2 project. This study attempts to analyze how the implementation of public sector coordination in the Patuha 2 project within the PPP framework. This study uses a descriptive-qualitative method with the interview method as a means of data collection. The results of the study indicate that the implementation of public sector coordination is still not running effectively and optimally.